Marriage Dispensation in Indonesia on The Perspective of Maqāṣid Al-Usrah - Sanuri Sanuri (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
Currently, the number of early marriage or underage marriage in Indonesia has increased sharply. In 2020, there are approximately 34,000 applications for marriage dispensation to the courts.. Of that number, 97% of the requests were granted. This means that almost all applicants for marriage dispensation are granted by the courts. Therefore, to measure whether the dispensation of the underage marriage has met the standart of mas}lah}ah for the perpetrator or not, it will be analyzed using the theory of maqāṣid al-usrah. The results of the research state that: (1) the motives for conducting underage marriage are due to economic factor, government policy to close schools during the Covid-19 pandemic, the rise of glorification of marriage on social media, and incidents of pregnancy out of wedlock; (2) giving dispensation by the courts to the applicants to continue conducting underage marriage is legally valid as fiqh al-munākaḥāt fiqh (Isalmic jurisprudence on marriage), but it can turn into ḥarām if the potential of harm is greater than the benefit for the bride and groom.